OCHRONA PRAW CZŁOWIEKA W GLOBALNYM ŚWIECIE NA PRZYKŁADZIE DZIAŁALNOŚCI FREE WEST PAPUA CAMPAIGN POLAND - Dombrowska, Kamila (Studia Europaea Gnesnensia, 2018)
Globalization processes entail increased flow of people, ideas and commodities,which to a certain degree are independent of limitations imposed by temporal and spatial barriers. The aim of this paper is to present practices which take advantage of opportunities resulting from globalization, on the example of Polish involvement in human rights protection in the Republic of Indonesia.